KAJIAN EKONOMI PENGUSAHAAN MINYAK TENGKAWANG DI KALIMANTAN BARAT: KASUS BATU LAYANG - O. K. Karyono; Hariyatno Dwiprabowo; Boen M. Purnama (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Tengkawang (illipe) oil is an important non-wood product in West Kalimantan Province. This oil is produced from illipe nut by processing it using a simple pressure technique. lllipe oil production in West Kalimantan in 1992 was 5,358 tonnes and as many as 341 tonnes had been exported with the export value of not less than Rp, 21 bilitons.The study showed that production cost of illipe oil per ton was Rp. 1.963,245. Gross revenue received by representative illipe oil plant was Rp. 7, 464, 111.620 per year.Break even point (BEP) in illipe oil production was 1,260. 00 kg per day or Rp. 786,744.00 per day. This means that to achieve BEP, the plant should produced illipe oil at least 25.78% of its installed capacity or around 181,69 ton per year.